UJI KELAYAKAN USAHA PETERNAKAN AYAM RAS PETELUR MENGGUNAKAN ANALISIS SENSITIVITAS DAN MATRIKS BOSTON CONSULTING GROUP - Dimas Aditya, (2022)
Barokah Laying Hens Farm which is located in Kalibeji Village, Sempor District, Kebumen Regency, Central Java, is a business that breeds laying hens with a maximum capacity of 3000 chickens that produce eggs. The egg production rate has decreased drastically because the chicken population was reduced during the Covid-19 pandemic due to prices of pullets, feed, and medicines was rising while the selling price of eggs tends to decrease over time. These problems motivated the researchers to analyze business feasibility by reviewing the values of NPV, IRR, PP and PI for financial aspects as well as several other feasibility aspects, also analyzing the sensitivity of 3 possible scenario, optimistic, best, or pessimistic state. Analysis was also carried out using the Boston Consulting Group matrix to determine the position of Barokah Farm in the market, as well as the appropriate strategy to be taken by farmers in dealing with their current problems. The results of the sensitivity analysis that the business is feasible to run with optimistic and best criteria. The results of the BCG matrix analysis show that Barokah Farm has a weak ability both in terms of growth rate and market share, and belongs to IV-Dogs quadrant.